A Comparative Analysis of Customers’ Satisfaction of Telecommunications Industries: A Reference from Bangladesh - Ahsan , Mohammad Kamrul (Global Disclosure of Economics and Business, 2017)
This is basically an analytic paper. Here the researcher has made a comparative analysis of customers’ satisfaction of Banglalink, Grameen Phone, Robi and Teletalk Telecommunication Companies in Bangladesh. An ordered questionnaire is organized to collect primary data from 400 customers from the customer care centers in the Sylhet City from Bangladesh. The researcher uses random and convenience sampling methods in this paper to collect data. The researcher selects fifteen independent variables to compare the customers’ satisfaction. Descriptive statistics, t-statistics, and ANOVA have been used in here to analyze the data. The findings have shown that the customers of Robi Telecommunication Company are more satisfied than the other companies. The researcher has thought that this effect may be the effect of merging with Robi and Airtel.